Computer-aided Affinity Enhancement of a Cross-reactive Antibody against Dengue Virus Envelope Domain III - Jonniya, Nisha Amarnath; Poddar, Sayan; Mahapatra, Subhasmita; Kar, Parimal (Cell biochemistry and biophysics, 2023)
The dengue virus (DENV), composed of four distinct but serologically related Flaviviruses, causes the most important emerging viral disease, with nearly 400 million infections yearly. Currently, there are no approved therapies. Although DENV infection induces lifelong immunity against the same serotype, the antibodies raised contribute to severe disease in heterotypic infections. Therefore, understanding the mechanism of DENV neutralization by antibodies is crucial in the design of vaccines against all serotypes. This study reports a comparative structural and energetic analysis of the monoclonal antibody (mAb) 4E11 in complex with its target domain III of the envelope protein for all four DENV serotypes. We use extensive replica molecular dynamics simulations in conjunction with the binding free energy calculations. Further single point and double mutations were designed through computational site-directed mutagenesis and observed that the re-engineered antibody exhibits high affinity to binding and broadly neutralizing activity against serotypes. Our results showed improved binding affinity by the gain of enthalpy, which could be attributed to the stabilization of salt-bridge and hydrogen bond interactions at the antigen-antibody interface. The findings provide valuable results in understanding the structural dynamics and energetic contributions that will be helpful to the design of high-affinity antibodies against dengue infections.